Approved revenue recurrent and capital estimates, 1996 - Federal republic of Nigeria; Federal republic of Nigeria (Lagos : The federal government press, 1996)
This book is the 1996 fiscal year approved current revenue and capital estimates of the federal government of Nigeria.
Title from cover.
osa; 25/04/2018
Loans
Keywords: Revenue; Nigeria